Poland Syndrome Case Study - KONUK, Suat (Archives of Clinical and Medical Case Reports, 2019)
Poland syndrome describes the congenital absence of the pectoralis major and minor muscles on one side of the body accompanied by chest and upper extremity deformities on the same side. However, the only constant finding of the syndrome is the absence of the sternocostal component of the pectoralis major muscle. This finding may be accompanied by additional findings on the same side such as absence of pectoralis minor muscle and of ribs 2 to 5, under-development of breast tissue, latissimus dorsi, serratus anterior and external oblique muscles. The incidence is approximately 1 in 30 000 live births and is more common in men than in women. It mostly holds the right hemithorax of the body. Here we present a 20-year-old male patient without complaints, diseases or other functional anomalies, who has hypoplasia of the right hemithorax, palpation indicating hypoplasia of the pectoral muscle group, and thoracic CT is showing a lack of pectoral muscles.